Analysis of electrical insulation paper by Simulation for analyze Polarization and Depolarization current testing method - Rakkaphan, Chananut; Boonsaner, Nutthaphan; Pattanadech, Norasage; Chancharoensook, Phop (My University, 2023)
This paper presents the quality analysis of insulation paper in distribution transformer oil in Thailand. The country locates in tropical zone and therefore experiences relatively high temperature. Analytical principles based on polarization and depolarization current method with various test conditions are used. Computer simulation can help to analyze the efficiency of insulation paper in transformer oil under different voltages and temperatures. The tested system consists of an electrode inside a high-Temperature and high-voltage control cabinet. It can be concluded that increasing temperature has a marginal effect on the electric field stress of the electrode. However, the rising temperature significantly affects the polarization current that flows through the insulators. The results can indicate the limitation of using oil insulation paper and how to improve the quality of it.
Keywords: dielectric strength; electric field stress; insulation paper; polarization and depolarization current; transformer oil